Pengaruh Brand Image dan Product Quality terhadap Purchasing Decision Produk Lipstik Wardah di Kota Sukabum - Sherra Adistiana Rizki Utami; Nina Wija Ratna (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2019)
This study aims to determine the effect of brand image and product quality on purchasing decision of Wardah lipstick products in Sukabumi City. This type of research is quantitative research. The population is Wardah lipstick customers in Sukabumi City. The number of samples is 100 respondents. The sample selection technique used was purposive sampling. Technical quality testing tools include test validity and reliability, classical assumptions, and the analysis technique used is multiple linear regression T test, and F test using IBM SPSS Statistics 24 program. The results of the t-test research (partially) show that there is no influence between the brand image on purchasing decision. Product quality is partially positive and significant for purchasing decision, while simultaneously, brand image and product quality have a positive and significant effect on purchasing decision.